The impact of agricultural and service sector output on economic growth in Vietnam - Khang, Nguyen The (International Journal of Innovative Research and Scientific Studies, 2025)
This study analyzes the role of agriculture and service sectors in Vietnam’s economic growth using an autoregressive distributed lag model with data from 1990 to 2023. In the context of Vietnam’s economic transition from an agriculture-based economy to industrialization and modernization, which are key national strategic objectives, this research aims to evaluate the critical economic factors influencing this transformation. Variables such as agriculture, services, exports, foreign direct investment, and population are examined to assess their short- and long-term impacts. The findings reveal that agriculture, despite being a traditional economic foundation, has a negative long-term impact due to its reliance on raw output and lack of modernization, which hinders growth. By contrast, the service sector exhibits a strong positive impact, reflecting urbanization trends and rising demand for knowledge-based services, making it a pillar of sustainable development. Exports show a negative long-term impact but a positive short-term effect, as Vietnam primarily exports low-value goods. Foreign direct investment contributes to growth through capital and technology transfers, whereas population dynamics do not have a significant impact because of the declining young workforce. This study underscores the necessity of transitioning from traditional to modernized agriculture, enhancing value-added production, and developing knowledge-based services. Policy recommendations focus on modernizing agriculture, optimizing foreign direct investment utilization, and fostering linkages between agriculture and services to ensure sustainable growth aligned with Vietnam’s global integration strategy.